1091. Incidence of Post-Transplant Lymphoproliferative Disorders among Epstein-Barr Virus Donor Positive, Recipient Negative Adult Solid Organ Transplant Recipients. (31st December 2020) - Limaye, Abhijit P; Heldman, Madeleine R; Edlefsen, Kerstin L; Kapnadak, Siddhartha G; Rakita, Robert M; Fisher, Cynthia E
Abstract: Background: Epstein-Barr virus (EBV) donor positive (D+), recipient negative (R-) serostatus is a major risk factor for post-transplant lymphoproliferative disorder (PTLD) in adult solid organ transplant recipients (SOTR). Few studies have systematically characterized absolute organ transplant type-specific incidence, timing, and outcomes of PTLD in adult EBV D+R- SOTR. Methods: We retrospectively assessed the incidence, timing, and associated morbidity and mortality of biopsy-confirmed PTLD (WHO classification) among consecutive adult SOTR between Jan 1, 2000 and Apr 30, 2018 at a single university center, and who had a minimum 2 years of follow-up. Antibodies to EBV (viral capsid antigen and nuclear antigen) were assessed in candidates and donors by FDA-cleared ELISA assay. Donors with unknown serology were considered seropositive based on the known prevalence of >93% seropositivity in this donor population. Results: Among 4, 923 SOTR, prior to transplant, 4, 770 (96.9%) were R+ (regardless of donor status), 144 (2.9%) were D+R-, and 9 (0.2%) were D-R-. PTLD incidence by last follow-up was higher among D+R- (15/144 [10.4%]) than R+ (61/4, 770 [1.2 %]), P < 0.0001, and occurred earlier after transplant (median 9.6 months [IQR 6.1-34.2] versus 35.1 months [IQR 7.1-73.1]), P = 0.003, respectively. Among D+R-, incidence was higher among recipients of non-kidney versus kidney organs (13/89 [14.6%] vs. 2/55 [3.6%], P = 0.05, respectively). Incidence in rank order was: pancreas (2/9 [22.2%]), lung (6/29 [20.7 %]), heart (2/21 [9.5%]), and liver (3/30 [6.7%]). PTLD histopathology was monomorphic in 9/15 [60%] and EBV-encoded RNA-1 (EBER-1) positive in 12/12 evaluable cases. Outcomes among the 15 PTLD cases included: graft failure without transplant in 3 (20%), graft failure with re-transplant in 2 (13.3%), and death within 6 months in 3 (20%). Table 1: Characteristics of the EBV Donor seropositive, Recipient seronegative (D+R-) cohort Figure 1: Cumulative Incidence of PTLD among the EBV D+R- cohort (all organs) Figure 2: Incidence of PTLD among the D+R- cohort, stratified by organ transplant type Conclusion: Although rare overall, we identified a specific subgroup of adult SOT patients (EBV D+R- non-kidney recipients) whose absolute PTLD incidence and associated morbidity and mortality are high, and who should be targeted for future mechanistic or therapeutic studies. Disclosures: All Authors : No reported disclosures